Actual problems of the usage of composite and hybrid materials based on different forms of nanocarbons in electromagnetic and biomedical applications - Maksimenko, Sergey A.; Kulahava, Tatyana A.; Okotrub, Alexander V.; Suslyaev, Valentin I. (Journal of the Belarusian State University. Physics, 2023)
A brief review of actual problems of present-day applied electromagnetism (wireless communication and information channels protection from unauthorised access, electromagnetic compatibility, biomedicine, etc.) which can be solved exploiting composite nanomaterials are presented. The importance has been outlined of applied developments exploiting different mechanisms of fine tuning of custom properties of carbon-based nanostructures, such as functionalisation, doping, complexing and hybridisation. The review stresses the necessity in practical implementation novel methods of composite and hybrid materials synthesis utilising 3D printing, modified CVD and other chemical technologies, as well as new types of composites such as foams and aerogels, sponges, hollow microstructures, core – shell structures with different chemical compositions, gradient structures. The review includes a wide list of references to recent original and review publications on nanocarbon based composite materials. This list can be helpful both for university lecturers, and young scientists ether choosing an ambition research topic or aimed at a concrete task in the field of electromagnetic wave interaction with nanostructures. It has been noted that the priority development rate of advanced industrial sectors, such as communication and biomedical technologies, requires essential intellectual and financial investments in fundamental and applied research and also enhancement of educational technologies, first of all – on the base of present-day experimental facilities and research-educational complexes. The review has been compiled on the basis of the results presented at the 6th Belarusian-Russian seminar-conference «Carbon nanostructures, thin films, and composites: synthesis, physical-chemical properties and applications».